Hubungan Obesitas Dengan Terjadinya Osteoartritis Lutut Pada Lansia Kecamatan Laweyan Surakarta - Nugraha, Annas Syahirul, dr. Sigit Widyatmoko, Sp. PD, M. Kes, dr. Safari Wahyu Jatmiko (2015)
The prevalence of osteoarthritis in Indonesia reached 15.5% in men and 12.7% in women. Osteoarthritis is a degenerative joint disease that is associated with damage to the articular cartilage. Obesity is excess body weight exceeds normal weight. Obesity is a risk factor for osteoarthritis of the knee due to the weight gain that resulted in the knee joint work harder. Some other factors that may cause osteoarthritis include age, gender, genetic, and work. This type of research, including analytical observational cross-sectional study approach. The number of samples examined 50 of 25 elderly obese and 25 non- obese elderly. The instruments used in the study include scale weight, height gauges and criteria for osteoarthritis of the knee joint by the American College of Rheumatology. The data obtained were analyzed using chi-square test with SPSS version 22 windows based. Based on the analysis of data using chi-square test showed p = 0.001 (p <0.005), which means that there is a relationship of obesity with the occurrence of knee osteoarthritis in the elderly in Surakarta Laweyan.